1989
DOI: 10.1161/01.atv.9.2.154
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of sulfated glycosaminoglycans and cholesterol content in normal and arteriosclerotic human aorta.

Abstract: Sulfated glycosaminoglycans were extracted from arteriosclerotic and adjacent nonarteriosclerotic areas of human aortas from persons ages 28 to 83 years; the glycosaminoglycans were compared with the cholesterol and triglyceride content of the tissues. Sulfated glycosaminoglycans were isolated after proteolytic digestion of defatted arterial tissue and were quantified after reductive labeling with NaB3H4. The amount of glycosaminoglycans in the aorta increased with the age of the person and the cholesterol con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
1
2

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 22 publications
3
40
1
2
Order By: Relevance
“…8 -10 A series of in vivo and in vitro studies support this hypothesis. [11][12][13][14][15][16][17][18] The interaction with chondroitin sulfate (CS)-rich PGs in the arterial intima contributes to the retention of apoB-containing lipoproteins in the vessel wall. This process may be a first step in a sequence of events leading to further modification of LDL particles in situ, such as oxidation and aggregation.…”
mentioning
confidence: 99%
“…8 -10 A series of in vivo and in vitro studies support this hypothesis. [11][12][13][14][15][16][17][18] The interaction with chondroitin sulfate (CS)-rich PGs in the arterial intima contributes to the retention of apoB-containing lipoproteins in the vessel wall. This process may be a first step in a sequence of events leading to further modification of LDL particles in situ, such as oxidation and aggregation.…”
mentioning
confidence: 99%
“…Similar changes in the exteracellular matrix of vessel walls have also been found in atherosclerosis 25 . It has been suggested that microalbuminuria is a marker of vascular damage and thus is an early finding in atherosclerosis 26 . The increased microalbuminuria observed in our study points towards the vascular damage in the patients with CAD as well as diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…25 The most abundant glycosaminoglycan side chains are chondroitin sulfate and dermatan sulfate, both of which are increased in atherosclerosis, as well as heparan sulfate. 42 Biglycan and versican have been extensively studied for their role in lipoprotein retention because they i) have strong affinity for chondroitin and dermatan sulfate proteoglycans, 42 ii) are enriched in areas of atherosclerosis, 42 and iii) bind to apoB100-containing lipoproteins. 43 Biglycan has emerged as the most important core protein involved in the initial lipoprotein retention because it localizes to areas of lipoprotein retention before lesion development.…”
Section: Discussionmentioning
confidence: 99%
“…It can bind lipoproteins in vitro, but it tends to localize to areas that are devoid of atherosclerotic lesions. 42 Although it is well established that Bruch's membrane is a pentilaminar structure composed of the RPE basement membrane, the inner collagenous layer, middle elastic layer, outer collagenous layer, and choriocapillaris basement membrane, less is known about its proteoglycan content. Hewitt et al 46 have identified a change in glycosaminoglycan content from its normal level of 77% chondroitin/dermatan sulfate and 23% heparan sulfate proteoglycans to 42% chondroitin/dermatan sulfate and 58% heparan sulfate with aging, and similarly 45% chondroitin/dermatan sulfate and the 55% heparan sulfate content in AMD.…”
Section: Discussionmentioning
confidence: 99%